Aspects of creation : the Water in the Wilderness motif in the Psalms and the Prophets - Klopper, Frances (Old Testament Essays, 2005)
The Water in the Wilderness motif is found in all genres of the Hebrew Bible. Literary motifs are rooted in real-life experiences and considering the barrenness of their country, this motif arose from the Israelites' daily witnessing of springs gushing forth in the rb'd.mi . The motif occurs in three divergent contexts: in 'historical' texts dealing with the desert wandering following the exodus; in creation texts with a mythological background (mainly in the Psalms) and in prophecy dealing with recreation and restoration after the exile. In the mythological texts, creation takes place once the initial watery chaos has been defeated and limited within boundaries, only to be let out again in a controlled manner in the form of springs to sustain the earth. In the prophetic texts, the Syrian desert separating Babylon from Palestine represents the chaos, feared by all, but rendered harmless by the divine production of springs to ensure a safe return journey to where a recreated future is envisioned.
free